Implementation of Digital-Based Learning in the Independent Curriculum at Elementary School in Bima City - Hairunisa, Hairunisa; Haryono, Haryono; Waluyo, Edi (Universitas Negeri Semarang, 2023)
Learning in the era of industrial revolution 4.0 demands a change from conventional learning systems to modern digital-based learning systems. The need for human adaptation to new technology is very necessary. This research aims to analyze the implementation of learning and the results of implementing digital-based learning in the independent curriculum at elementary school level in Bima City. The benefit of research is that it can be used as a reference and evaluation for the education sector regarding the implementation of digital-based learning in the independent curriculum. This research is qualitative research using phenomenological studies and subjective research types. The data collection techniques used in this research consist of interview, observation and documentation techniques. The triangulation technique used in this research consists of two, namely technical triangulation and source triangulation. Data analysis techniques consist of data collection, data reduction, data presentation, and data verification. The results of this research are that the implementation of digital-based learning in the independent curriculum has been effectively implemented. Every school, even every class, has a different way of implementing it. However, there are several obstacles faced, namely the number of LCD is still insufficient, the internet network is less stable, and there are several teachers who experience difficulties in creating digital-based learning devices. These obstacles are not an obstacle for teachers because every teacher has effective strategies. The strategy used to overcome these obstacles is by using a smartphone or using an LCD in rotation, using a personal quota, and continuing to upgrade oneself. The benefit of research is as a reference and evaluation regarding the implementation of digital-based learning in the independent curriculum.